DUAL FUNCTIONAL PIEZOELECTRIC DEVICE FOR INCREASING THE EFFICIENCY OF FERMENTATION PROCESSES - SUDIREDDY, Bhaskar Reddy; SANTUCCI, Simone (2025)
A fermentation enhancement device for use in a bioreactor, the fermentation enhancement device comprising: an electrical charge structure defining an inner volume arranged for accommodating a fermentation process, the electrical charge structure comprising: a piezoelectric proliferation layer exposed to the inner volume; and a piezoelectric virucidal layer arranged at an outer surface of the electrical charge structure; an opening configured to allow therethrough a flow of nutrients and/or bacteria; wherein the fermentation enhancement device is arranged such that actuation of the electrical charge structure, by an actuation source, generates an electrical charge at the virucidal layer that kills and/or inactivates viruses, and an electrical charge at the proliferation layer that stimulates bacterial growth. Un dispositif d'amélioration de fermentation destiné à être utilisé dans un bioréacteur, le dispositif d'amélioration de fermentation comprenant : une structure de charge électrique définissant un volume interne agencé pour recevoir un processus de fermentation, la structure de charge électrique comprenant : une couche de prolifération piézoélectrique exposée au volume interne ; et une couche virucide piézoélectrique disposée au niveau d'une surface externe de la structure de charge électrique ; une ouverture conçue pour permettre à travers celle-ci un flux de nutriments et/ou de bactéries ; le dispositif d'amélioration de fermentation étant agencé de telle sorte que l'actionnement de la structure de charge électrique, par une source d'actionnement, génère une charge électrique au niveau de la couche virucide qui tue et/ou inactive des virus, et une charge électrique au niveau de la couche de prolifération qui stimule la croissance bactérienne.